PREDICTING THE ADOPTION OF INSURTECH AMONG GENERATION Z IN INDONESIA - Umran, M. Fankar; Sadat, Andi Muhammad; Maupa, Haris (International Journal of Application on Economics and Business, 2024)
The emergence of Insurtech services in Indonesia has been a transformative force, changing how insurance companies operate and reach their customers. However, most insurance companies still use conventionally by relying on agents and brokers to provide insurance purchases and payments. The success and growth of the insurance industry require technological support to make the process efficient and profitable. This research aims to empirically identify the factors that influence insurance industry customers to adopt Insurtech services among Generation Z in Indonesia, which is known to be technologically literate and reaches 28% of the total population. This research is quantitative, where the research questionnaire will be distributed using Google Forms to a minimum of 310 respondents based on the Cochran formula. Six hypotheses were developed based on the literature and will be tested using the Structural Equation Modeling (SEM) approach with software AMOS version 23. The results are expected to contribute to academics, insurance companies, and regulators regarding the determining factors for the adoption of Insurtech services in Indonesia.